The Influence of Broken Home Families on Student Social Behavior at SMAN 15 Padang Odd Semester 2024/2025 Academic Year - Dhieva Nur Mulia Wa Lasky Vukuoka; Linda Fitria; Popi Radyuli (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Influence of Broken Home Families on Student Social Behavior at SMAN 15 Padang Odd Semester Academic Year 2024/2025, Bachelor of Counseling Guidance Education, Faculty of Teacher Training, Universitas Putra Indonesia ''YPTK'' Padang. This study aims to determine the influence of broken home families on the social behavior of students at SMAN 15 Padang in the odd semester of the 2024/2025 school year. The type of research uses quantitative. The population and research sample amounted to 32 people who were taken using total sampling. This study examines the influence of broken home families on social behavior. The instrument used in this study for data collection is a questionnaire prepared according to the Likert model. The data analysis was carried out using statistical programs on the SPSS 29 computer and Microsoft Excel. Based on the results of the hypothesis with and with a table r value of 0.3494, it can be said that r value 0.536 > 0.3494 table r value, it can be concluded that the hypothesis is accepted, meaning that there is a significant influence between the broken home family and the social behavior of grade XI students of SMAN 15 Padang.